MicroRNA Targeting to Modulate Tumor Microenvironment - Kuninty, Praneeth R.; Schnittert, Jonas; Storm, Gert; Prakash, Jai (Frontiers in Oncology, 2016)
Communication between stromal cells and tumor cells initiates tumor growth, angiogenesis, invasion, and metastasis. Stromal cells include cancer-associated fibroblasts, tumor-associated macrophages, pericytes, endothelial cells and infiltrating immune cells. MicroRNAs (miRNAs) in the tumor microenvironment have emerged as key players involved in the development of cancer and its progression. miRNAs are small endogenous non-protein-coding RNAs that negatively regulate the expression of multiple target genes at the posttranscriptional level, thereby control many cellular processes. In this review, we provide a comprehensive overview of the identified miRNA targets in different stromal cells and their impact on the regulation of intercellular crosstalk within the tumor microenvironment. We also discuss the therapeutic significance of miRNA targets in modulating the tumor microenvironment. Since delivery of miRNA is quite challenging and the biggest hurdle for their clinical translation, we review various miRNA delivery systems that can potentially be used for targeting miRNA to stromal cells within the tumor microenvironment.